The Effect of the Problem Based Learning Model on Students' Problem-Solving Ability and Scientific Attitude - Sri Handayani; Suyanta Suyanta (Postgraduate, University of Mataram, 2024)
This study aims to analyze significant differences in problem-solving skills and scientific attitudes between students who learn using the Problem Based Learning model and students who learn using the Discovery Learning model and determine the effective contribution of learning using the PBL model developed to students' problem-solving skills and scientific attitudes simultaneously. This research approach uses a quantitative research approach with a quasi-experimental method. The research population is 5 classes of students in grade XI MIPA Malinau for the 2023/2024 academic year. The sample was determined by random sampling technique against the class. Based on the random results, class XI MIPA1 was selected as a group of students using the Problem Based Learning learning model and class XI Mipa 3 using the Discovery Learning learning model. Data on problem-solving ability were collected by tests, while scientific attitudes were collected by questionnaires. The data was analyzed by One way Multivariate. The results of the study showed that: (1) there was a significant difference in problem-solving ability and scientific attitude between students who learned with the Problem Based Learning model and students who learned with the Discovery Learning model; (2) the effective contribution of learning using the PBL model to problem-solving ability and scientific attitude simultaneously was 0.46 or 46.1%.